2013
DOI: 10.1080/10640266.2014.857522
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight as a Prognostic Factor for Day Hospital Success in Adolescents With Anorexia Nervosa

Abstract: For female adolescents with anorexia nervosa, body weight at admission as a predictor of treatment outcome in the day hospital setting was examined. A retrospective review of patient charts was completed to determine success or failure in the day hospital program based on weight above or below 85% of ideal body weight. There was not a greater risk of failure in the day hospital program for patients with ideal body weight below 85% compared to those patients with an ideal body weight of ≥ to 85%. Body weight di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 16 publications
1
24
0
2
Order By: Relevance
“…It is not always clear in the literature which programs require full time attendance and which taper down attendance to allow engagement with real life. However, our review of the literature suggests that mean attendance of 30 days is lower than some programs (e.g.,Grewal et al, —200.4 days; Ngo & Isserlin, —81.9 days) though comparable with others (Ornstein et al, —33.3 days) including the average length of stay for AN group (11.94 weeks) in the Ornstein et al () study. Discharge from ITP is clinically determined, but clinical need is determined in the context of it being a component of a comprehensive outpatient treatment program.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…It is not always clear in the literature which programs require full time attendance and which taper down attendance to allow engagement with real life. However, our review of the literature suggests that mean attendance of 30 days is lower than some programs (e.g.,Grewal et al, —200.4 days; Ngo & Isserlin, —81.9 days) though comparable with others (Ornstein et al, —33.3 days) including the average length of stay for AN group (11.94 weeks) in the Ornstein et al () study. Discharge from ITP is clinically determined, but clinical need is determined in the context of it being a component of a comprehensive outpatient treatment program.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast with other programs who have fixed discharge target weights (92.5%–100% IBW, Ngo & Isserlin, ; between 15th and 20th age adjusted centile, approximately corresponding to 88–90%mBMI, Herpertz‐Dahlmann et al, ; 100% of target weight, Grewal et al, ), the mean %mBMI (86.83%, range 65–116) for young people who completed ITP is more similar to the discharge weight in the Goldstein et al () 10 weeks fixed length day program (84.14%, SD 10.01). However it is worth noting that programs who had fixed weight targets as a criteria for the successful program completion also report high rates of young people disengaging from the program for example 38% (Dancyger et al, ) and 42% (Grewal et al, ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The Pubmed search resulted in 192 titles for inspection and 7 abstracts for inspection of which 5 were not trials of treatment setting [28][29][30][31][32] and one was a review [33] and one new trial [34] was identified. The CCRCT Issue 6 of 12, June 2014 (n = 797723) search resulted in 20 titles for inspection of which two were duplicates and one new trial [29] was identified ( Figure 1).…”
Section: Results Of Searchmentioning
confidence: 99%
“…Furthermore, younger age and comorbid PD seemed to be significant predictors for treatment dropout. One of the most striking results was that younger patients (17)(18)(19)(20)(21)(22)(23)(24) without a comorbid PD had the highest weight gain during treatment. This could not be observed in patients with a comorbid PD, who demonstrated the highest weight gain between 25 and 34 years of age.…”
Section: Introductionmentioning
confidence: 99%